Yield and Water Use of Siberian Wildrye with Ridge and Furrow Planting in Northern China. (1st November 2013) - Zhang, W.; Li, Z.; Gong, Y.; Lu, X.; Nielsen, D.C.
Abstract : Siberian wildrye ( Elymus sibiricus L.) is a perennial grass that is widely planted in semiarid northern China, but yield is often low due to insufficient soil water supply. Field experiments were conducted from 2009 to 2011 to study the effects of ridge and furrow planting (RFP) on yield, evapotranspiration, and water use efficiency (WUE) of Siberian wildrye grassland under rainfed conditions. The treatments included bare flat bed planting (FB), bare ridge with bare furrow (BRB), bare ridge with naked oat ( Avena nuda L.) straw mulch in furrow (BRM), plastic mulch on ridge with bare furrow (MRB), and plastic mulch on ridge with straw mulch in furrow (MRM). In the RFP system, the ridge and furrow were each 30 cm wide. Total forage yield with MRB and MRM each year was 46 to 111% and 50 to 135% greater, respectively, than with FB (2580 kg ha –1 yr –1 ). These two treatments also increased total WUE each year by 79 to 121% and 80 to 150%, respectively, compared with FB (10.8 kg ha –1 mm –1 yr –1 ). The BRB and BRM treatments increased total forage yield by 47 and 81% and total WUE by 51 and 81%, respectively, compared with FB only in 2010. The addition of straw mulch did not result in a further increase in total yield or WUE. Therefore, the MRB planting system will be recommended in Siberian wildrye production for achieving relatively high forage yield and WUE.